(untitled) (CIPEEX, 2025)
Viral hepatitis B and C are the most epidemiologically relevant subtypes in Brazil, with high morbidity and mortality rates due to their clinical characteristics and complications. The overall objective of this study is to describe the regions of Anápolis with the highest incidence of these types of hepatitis, provide data to improve public health and to develop an educational booklet. This study is quantitative, descriptive, observational, and cross-sectional, using secondary data from the Municipal Health Department, referring to the Viral Hepatitis Notification Unit in the municipality. The research included the analysis of medical records of patients with hepatitis B and C registered at the reference unit between 2019 and 2024. A prevalence of hepatitis B cases was found in the neighborhoods of the Central region of the city (n=25), Jundiaí (n=16), and Bairro de Lourdes (n=12), while hepatitis C cases were more prevalent in the Central region (n=17) and Maracanã (n=14). It was suggested that a specific code be created for each neighborhood, as well as a booklet with relevant information about these types of hepatitis, to be made available to the population. It was concluded that there were a greater number of cases in the central region of Anápolis; however, the study had limitations in terms of a more in-depth analysis of these data.